Letter: proton pump inhibitors and risk of myocardial infarction—authors' reply. Issue 1 (14th December 2021) - Nolde, Michael; Ahn, Nayeon; Dreischulte, Tobias; Rückert‐Eheberg, Ina‐Maria; Güntner, Florian; Günter, Alexander; Gerlach, Roman; Tauscher, Martin; Amann, Ute; Linseisen, Jakob; Meisinger, Christa; Baumeister, Sebastian‐Edgar
LINKED CONTENT: This article is linked to Nolde et al papers. To view these articles, visit https://doi.org/10.1111/apt.16565 and https://doi.org/10.1111/apt.16644